Queer youth experiences with abstinence-only-until-marriage sexuality education: "Can't get married so where does that leave me?" - Fisher, Christopher (2009)
Abstinence-only-until-marriage sexuality education has received increasing attention vis-a-vis policy, funding, and research. Despite large sums of federal money to develop, implement, and to some extent, assess abstinence-only education, virtually no studies have looked to assess the experiences of such a curriculum for gay and bisexual male youth. This qualitative study explores narratives from semi-structured interviews of eight self-identified gay and bisexual males who received an abstinence-only-until-marriage sexuality education. Their voices lend empirical evidence to the often cited but undocumented negative gay and bisexual male youth experiences with an abstinence-only sexuality education. These young men recount stories of silence, risk, hostility, and resiliency.